Sickness as a human trait. Towards a consideration of disease as existential phenomena (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this contribution we investigate the scope and consequences that arise from applying Heidegger in the field of philosophy of medicine. For this purpose, the paper is divided in the following points: First, we will make explicit the meaning of an “anthropologization” of Heidegger's thought. Second, an overview of the most significant contemporary theories of health and disease in the field of theory of medicine will be offered. Third, we will interpret the meaning of disease from a Heideggerian perspective. Finally, 4) we will offer some critical reflections offered in relation to the analysis.
Keywords: Health and disease; Heidegger; existential phenomenon; analytic of Dasein; human and animal.